2017
DOI: 10.1111/jocn.13761
|View full text |Cite
|
Sign up to set email alerts
|

Questioning skills of clinical facilitators supporting undergraduate nursing students

Abstract: Clinical facilitators should undertake targeted education that focuses on how to frame questions for students that demand application, analysis, synthesis and evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
1
17
0
3
Order By: Relevance
“…Whether during clinical placement or simulation-based learning, reflection and reflective learning in health professional education might be facilitated by clinical supervisors or educators. However, in some cases, these individuals might not be experienced at stimulating higher-order reflective thinking with effective questioning (Husebø, Dieckmann, Rystedt, Søreide, & Friberg, 2013;Philips & Duke, 2001;Philips, Duke, & Weerasuriya, 2017). Furthermore, considering when, where, and how debriefing is to occur during an extended period, as is the case for an SCP experience, requires consideration of models, timing, and spaces for debriefing to occur during an SCP that reflect the realities of an authentic clinical placement (Eraut, 2007;Herrington & Oliver, 2000).…”
Section: Debriefing and Reflectionmentioning
confidence: 99%
“…Whether during clinical placement or simulation-based learning, reflection and reflective learning in health professional education might be facilitated by clinical supervisors or educators. However, in some cases, these individuals might not be experienced at stimulating higher-order reflective thinking with effective questioning (Husebø, Dieckmann, Rystedt, Søreide, & Friberg, 2013;Philips & Duke, 2001;Philips, Duke, & Weerasuriya, 2017). Furthermore, considering when, where, and how debriefing is to occur during an extended period, as is the case for an SCP experience, requires consideration of models, timing, and spaces for debriefing to occur during an SCP that reflect the realities of an authentic clinical placement (Eraut, 2007;Herrington & Oliver, 2000).…”
Section: Debriefing and Reflectionmentioning
confidence: 99%
“…The clinical workplace is a highly complex social environment that provides invaluable experiences for student learning. Nurses are required to facilitate and supervise student learning, in addition to playing a role in assessing competency (Phillips et al ). However, clinical education is context dependant; the experience of learning in clinical practice differs widely from area to area.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the importance of listening to nursing students' accounts of their experiences, and of what they have observed from their clinical teachers, peers, patients and other health care workers [[i]]. In the study of rst-year nursing students, it was found that caring was not what they expected [19]. However, nursing students learned from their experiences and vowed to provide caring behaviours toward their patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, nursing students learned from their experiences and vowed to provide caring behaviours toward their patients. Therefore, it is important that clinical teachers model caring behaviours not only to the patients and their families, but also to students [19,24].…”
Section: Discussionmentioning
confidence: 99%